Toksyczność miedzi, cynku oraz kadmu, rtęci i ołowiu dla człowieka, kręgowców i organizmów wodnych = Toxicity of some trace metal - Piontek, Marlena; Fedyczak, Zuzanna; Łuszczyńska, Katarzyna; Lechów, Hanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The work concerns the toxicity of some heavy metals (trace): two belonging to microelements - Cu and Zn, and three are at the forefront of occupational and environmental poisons - Cd, Hg and Pb.
Keywords: metale śladowe; toksyczność; biologiczne testy toksyczności; metody bioindykacyjne; Daphnia magna; Dugesia tigrina; trace metals; the toxicity; biological toxicity tests; methods of bioindicative